"To Behold with Wonder": Theory, Theater, and the Collaboration of James Tenney and Carolee Schneemann. Issue 1 (16th January 2017) - SMIGEL, ERIC
Abstract: During their partnership between 1955 and 1968, composer James Tenney (1934–2006) and artist Carolee Schneemann (b. 1939) engaged in what initially appear to be opposing modes of practice. Tenney developed theories concerning the perception of musical form and composed rationalized works based on carefully calculated algorithms. Schneemann, by contrast, was driven by spontaneity and sensuality, and her provocative artworks vehemently address sexual, gender, and political issues. This duality was especially evident in the mid-1960s, when Tenney was conducting psychoacoustic research at Yale University and Schneemann was producing her first theater events in downtown New York. Although his compositional productivity declined during this period, he participated in several of Schneemann's projects, scripted a few theater pieces of his own, and wrote extensive notes on artistic form as a perceptual model of physiological processes. Drawing from unpublished archival documents and personal interviews, this article provides an overview of Tenney's relationship with Schneemann and demonstrates how his simultaneous involvement in theoretical research and theatrical performance transformed his creative work. A close examination of Tenney's scores, journals, and correspondence reveals that he was deliberately exploring the distinctions between abstraction and collage and seeking to reconcile the apparent dualism of theory and theater.